Behaviourally-inhibited temperament and female sex, two vulnerability factors for anxiety disorders, facilitate conditioned avoidance (also) in humans - Sheynin, Jony (2014)
Acquisition and maintenance of avoidance behaviour is a key feature of all human anxiety disorders. Animal models have been useful in understanding how anxiety vulnerability could translate into avoidance learning. For example, behaviourally-inhibited temperament and female sex, two vulnerability factors for clinical anxiety, are associated with faster acquisition of avoidance responses in rodents. However, to date, the translation of such empirical data to human populations has been limited since many features of animal avoidance paradigms are not typically captured in human research. Here, using a computer-based task that captures many features of rodent escape-avoidance learning paradigms, we investigated whether avoidance learning would be faster in humans with inhibited temperament and/or female sex and, if so, whether this facilitation would take the same form. Results showed that, as in rats, both vulnerability factors were associated with facilitated acquisition of avoidance behaviour in humans. Specifically, inhibited temperament was specifically associated with higher rate of avoidance responding, while female sex was associated with longer avoidance duration. These findings strengthen the direct link between animal avoidance work and human anxiety vulnerability, further motivating the study of animal models while also providing a simple testbed for a direct human testing.